What factors motivate male and female Generation Z students to become engaged as peer teachers? A mixed‐method study among medical and dental students in the gross anatomy course. Issue 4 (25th October 2021) - Messerer, David A. C.; Kraft, Sophie F.; Horneffer, Astrid; Messerer, Laura A. S.; Böckers, Tobias M.; Böckers, Anja
Abstract: Peer‐teaching is widely established in anatomy teaching and offers well‐described advantages. Nevertheless, at Ulm University, Germany, a reduction in the number of peer teacher applicants for the dissection course was observed. This study examined factors related to the attractiveness of a position as a peer teacher for Generation Z students. Participants of the gross anatomy course were asked to evaluate factors influencing the attractiveness of a peer teacher position using a six‐point Likert scale. Additionally, open‐ended questions were analyzed qualitatively. Sex‐specific subgroup analysis was performed comparing students of low and high motivation to apply for a tutorship. Of the 374 students who participated in this study (response rate 53%), 38% stated that they were intending to apply as peer teachers. Data indicated that students displayed intrinsic motivation to apply for a tutorship because of the opportunity to improve their anatomy knowledge and/or their pleasure in teaching. In contrast, extrinsic factors like remuneration of the tutorship and its relevance for their curriculum vitae were least important. Anatomy educators underestimated the demotivating factor of the workload associated with the tutorship and encouraged students less frequently to apply than peer teachers. Only minor sex‐specific differences could be identified. Nevertheless, female students were encouraged less frequently to apply than their male peers. In summary, Generation Z students apply as peer teachers because they are enthusiastic about the task. To motivate students to commit to extracurricular activities like a tutorship, anatomy educators should actively encourage students—particularly females—more frequently to apply.